Os mecanismos psicossociais e religiosos da mudança de igreja entre adolescentes e jovens católicos do Liceu de Artes e Ofícios/UNICAP - Velozo, Maristela Ferreira Silva (2007)
This dissertation has as a general purpose to identify and analyze which psychological, social and religious factors lead the young adult and teenagers to change their religion. The purpose is to identify through specific objectives, the young adult and teenager s religious identity, detecting their restlessness to find and change their religion or faith. Also, the real religious and familiar experiences of the sample selected was researched through the understanding of their holy religious experiences. It is possible to reflect over the psychological,social and religious factors that lead to the religion change through the identification and analyze of the religious phenomenon regarding the change of religion. The methodology consists of field research with the application of a 30 mix questions questionnaire applied to a randomly selected sample of 46 persons, from which 26 teenagers and 20 young adults of the Liceu de Artes e Ofícios / Unicap (Lyceum of Artes and Crafts of the Catholic University of Pernambuco). The sample selected comprehended youths with average age from 14 to 25 years, who were catholic and nowadays moved to a different religion, despite the family tradition. Based on the data collected, a quantitative analyze was performed using the percentage and other statistic instruments needed. The qualitative analyze of the life experience and representations was also performed, checking the theoretical basis and expecting a reliance of 95% and a 5% error possibility. It is noted in the results the need of a deeper teenager and young adult introspection in order to obtain a better understanding of their different religious and psychosocial values, which justify the research of the factors that lead them to change the religion. It is recognized that the teenager and young adult flexibility and instability phase are some of the reasons that cause the religion change of faith. Possible strategies aiming a better interaction with teenagers and young adults in the Catholic institutions (Christian communities and groups), who are facing a visible religious pluralism, can be detected through the analyze of the data collected. It was concluded that since the subject change of religions between teenagers and young adults is not deeply researched, the identification and analyze of the psychosocial and religious mechanisms may identify educational and pastoral strategies (familiar and scholar), in a realistic and critic way, facing the religions offer and actual modernity challenges, that will show to teenagers and young adults what is positive in the new and old religions, focusing the need of a more conscious and stable religious presence in their personality.